2020
DOI: 10.1099/jmm.0.001214
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance profiles of diarrhoeagenic Escherichia coli isolated from travellers returning to the UK, 2015–2017

Abstract: Introduction. Diarrhoeagenic Escherichia coli (DEC) are difficult to distinguish from non-pathogenic commensal E. coli using traditional culture methods. The implementation of PCR targeting specific virulence genes characteristic of the five DEC pathotypes, has improved the detection of DEC in faecal specimens from patients with symptoms of gastrointestinal disease.Aim. Antimicrobial resistance (AMR) profiles of 660 strains of DEC isolated between 2015 and 2017 from UK travellers reporting symptoms of gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…However, no CF was reported in Danish isolates whereas all Shenzhen isolates carried CS21. L4 lineage was also detected at low fraction (6%) in the global dataset (von Mentzer et al, 2014), and the subtyping combination of Shenzhen isolates, i.e., L4 (O25:H16, ST1491), was only identified in isolates from few travelers returning to the UK (Boxall et al, 2020) and from local diarrheal cases of China Pan et al, 2015;Li et al, 2017). Taken together, these results revealed that the major circulating ETEC lineages in Shenzhen, as well as in several other developed regions of China were distinctive, which are not the commonly detected global or endemic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…However, no CF was reported in Danish isolates whereas all Shenzhen isolates carried CS21. L4 lineage was also detected at low fraction (6%) in the global dataset (von Mentzer et al, 2014), and the subtyping combination of Shenzhen isolates, i.e., L4 (O25:H16, ST1491), was only identified in isolates from few travelers returning to the UK (Boxall et al, 2020) and from local diarrheal cases of China Pan et al, 2015;Li et al, 2017). Taken together, these results revealed that the major circulating ETEC lineages in Shenzhen, as well as in several other developed regions of China were distinctive, which are not the commonly detected global or endemic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature search for studies of ESBL-DEC, we omitted those not reporting total number of DEC 43 , 45 or strain-specific travel data 46 , 47 ; these reports prove existence of ESBL-DEC, though. Instead, we selected, in accord with our initial aim, papers providing prevalence data on resistance among travel-acquired DEC or rates of ESBL-DEC among DEC originating in LMICs.…”
Section: Resultsmentioning
confidence: 99%
“…54 Likewise, substantial rates (53 and 57%) of ESBL-EAEC have been reported among clinical EAEC isolates in England; yet they do not report which of the strains were travel-acquired nor their countries origin. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Enteroaggregative E. coli (EAEC) represents an important pathotype that belongs to the IPEC group, which is responsible for cases of acute and persistent diarrheal illness in developing countries and cases of travelers´ diarrhea [ 4–7 ]. EAEC strains are identified by the production of the aggregative adherence (AA) on cultured epithelial cells, which is characterized by adhered bacteria on the surface of epithelial cells and the coverslip between cells in an arrangement resembling stacked bricks [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%